1998
DOI: 10.1111/j.1540-8167.1998.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection Criteria in Implantable Defibrillators

Abstract: Programming sudden onset and stability detection criteria with a sustained rate duration safety net for triggering tachycardia therapy results in appropriate device management in most patients with supraventricular and slow (< 210 beats/min) ventricular tachycardias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 11 publications
0
53
0
1
Order By: Relevance
“…It withholds therapy if acceleration across the sinus-VT rate boundary is gradual. Because onset discriminators classify the rhythm only once, and thus cannot correct misclassifications, they are now used infrequently and only with an override feature and/or other discriminators [112][113][114][115]. Chamber of onset is a related, interval-based, dual-chamber discriminator that classifies a 1:1 tachycardia as SVT if the atrial rhythm accelerates at the device-defined onset.…”
Section: Rejection Of Sinus Tachycardia By Onsetmentioning
confidence: 99%
See 3 more Smart Citations
“…It withholds therapy if acceleration across the sinus-VT rate boundary is gradual. Because onset discriminators classify the rhythm only once, and thus cannot correct misclassifications, they are now used infrequently and only with an override feature and/or other discriminators [112][113][114][115]. Chamber of onset is a related, interval-based, dual-chamber discriminator that classifies a 1:1 tachycardia as SVT if the atrial rhythm accelerates at the device-defined onset.…”
Section: Rejection Of Sinus Tachycardia By Onsetmentioning
confidence: 99%
“…Because interval variability in conducted AF decreases at faster rates, stability becomes unreliable in discriminating VT from conducted AF at ventricular rates greater than 170 bpm [112,115]. Interval stability can also fail if drugs (e.g., amiodarone) cause monomorphic VT to become irregular or induce polymorphic VT to slow into the SVT-VT discrimination zone [114,117].…”
Section: Rejection Of Af By Ventricular Interval Regularitymentioning
confidence: 99%
See 2 more Smart Citations
“…These two algorithms have been traditionally underused due to concern of misclassification of a true VT as a nonshockable rhythm by the device, thereby continuously withholding a necessary therapy. However, several publications have demonstrated that programming sudden onset and stability detection criteria with a sustained rate duration safety net for triggering tachycardia www.intechopen.com therapy results in appropriate device management in most patients with supraventricular and slow ventricular tachycardias (Brugada et al, 1998). Recent data from the MADIT II trial (Daubert et al, 2008) showed that the stability detection algorithm was programmed less frequently in patients receiving inappropriate shocks (17% v s .…”
Section: Stabilitymentioning
confidence: 99%